Pengaruh Pengukuran Balance Scorecard (BSC) Terhadap Kinerja Pegawai : Studi Pada Pegawai Bank Bjb Cabang Banjar - Asri Afriyanti; Enas Enas; Aini Kusniawati (Ebisnis Manajemen, 2024)
The aim of this research is to analyze and describe: 1). Implementation of the Balanced Scorecard at Bank Bjb Banjar Branch in the 2nd quarter of 2023; 2) Results of measuring the performance of Bank bjb Banjar Branch employees in the 2nd quarter of 2023; 3) The influence of the Balanced Scorecard measurement on employee performance at Bank Bjb Banjar Branch in the 2nd quarter of 2023. The research method used in preparing this thesis is descriptive with a quantitative approach. The data collection technique was carried out by distributing questionnaires to 52 employees who were the population and sample in this research. The research results show that BSC measurements have a positive and significant effect on employee performance, meaning that the more optimal the BSC measurement results are, the more optimal the employee performance will be.